SAMHSA to write new application for new SOR with stimulants included. Issue 2 (10th January 2020) - Knopf, Alison
Abstract : The addition of stimulants as an allowable use for State Opioid Response (SOR) grants will require a new application, which the Substance Abuse and Mental Health Services Administration (SAMHSA) is working on, ADAW has learned. The change was in the FY 2020 appropriations bill passed last month by Congress (see ADAW, Dec. 23, 2019; "FY 2020 Appropriations: Stimulants added to SOR's $1.5 billion, " https://onlinelibrary.wiley.com/doi/10.1002/adaw.32573 ), along with funding for other SAMHSA programs, including the Substance Abuse Prevention and Treatment block grant (SAPT BG). After the bill passed before Christmas, Washington went away for the holidays.